Preparation method and application of hydrophobic La / SiO2 (at) DA composite aerogel

The hydrophobic La/SiO2@DA composite aerogel prepared by the sol-gel method uses S-M bonds, hydrogen bonds and π-π stacking mechanisms to efficiently adsorb thiophene compounds, which solves the removal of thiophene sulfides in the prior art. The problems of low efficiency and poor stability of hydrophilic aerogels have achieved high selectivity and efficient desulfurization effects, which are convenient for industrial application.

CN119236882AInactive Publication Date: 2025-01-03ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411524171.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is inefficient and costly when removing thiophene sulfides from aromatic hydrocarbons. The structure collapses in a humid environment, and the selectivity is reduced, and the adsorption of aromatic hydrocarbons and polar compounds also leads to a decrease in aromatic yield. .

Method used

The hydrophobic La/SiO2@DA composite aerogel was prepared by sol-gel method combined with atmospheric pressure drying technology. The thiophene compounds were effectively adsorbed through the S-M bond, hydrogen bond and π-π stacking mechanism, and the stability was maintained at room temperature. Suitable for high selective desulfurization.

Benefits of technology

It realizes efficient adsorption of thiophene compounds, maintains adsorption performance in humid environments, reduces equipment requirements and process complexity, facilitates industrial production, and improves the yield and selectivity of aromatic hydrocarbons.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108748690000061
    Figure BDA0005108748690000061
  • Figure BDA0005108748690000071
    Figure BDA0005108748690000071
  • Figure BDA0005108748690000091
    Figure BDA0005108748690000091
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a hydrophobic La / SiO2 (at) DA composite aerogel. The aerogel is prepared by combining a sol-gel method with a normal-pressure drying technology, and the preparation method comprises the following specific steps: dissolving dopamine hydrochloride in water, adding a hydrophobic silicon source (methyl triethoxysilane) and absolute ethyl alcohol, and stirring and hydrolyzing under an acidic condition to obtain hydrophobic silica sol; the preparation method comprises the following steps: adding SiO2 (at) DA into a reaction kettle, stirring, adjusting pH, standing in a water bath, adding an aging solution to enhance a skeleton structure, grinding gel, adding n-hexane and lanthanum nitrate hexahydrate, stirring, and drying to obtain the hydrophobic La / SiO2 (at) DA composite aerogel. And then the adsorbent is applied to adsorption and removal of thiophene sulfides in simulated aromatic hydrocarbons. The hydrophobic La / SiO2 (at) DA composite aerogel adsorbent disclosed by the invention has good hydrophobicity, so that the hydrophobic La / SiO2 (at) DA composite aerogel adsorbent still has relatively high adsorption selectivity on thiophene compounds when being used for adsorbing aromatic hydrocarbon products containing water and polar compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel preparation, and specifically relates to a preparation method and application of a hydrophobic La / SiO2@DA composite aerogel. Background Art

[0002] Aromatics produced by petroleum processing play an extremely important role in many fields. In industrial applications, they can be used as key raw materials for synthesizing polymer materials such as plastics, rubber, and fibers, and as excellent solvents in industries such as coatings, inks, and pesticides. In the energy field, aromatics such as toluene and xylene can increase the octane number of aromatics, enhance anti-knock performance, and make the engine run more smoothly and efficiently. Clean and efficient fuels can also be produced by processing aromatics to reduce the pollution of exhaust emissions to the environment. In the pharmaceutical field, many drug syntheses require aromatics as starting materials or intermediates, such as antibacterial drugs and anticancer drugs. However, aromatics produced by petroleum processing often contain sulfides. The presence of sulfides will poison the catalyst in the subsequent processing process and reduce the activity and life of the catalyst. In addition, aromatics that do not contain or contain less sulfur can better play their characteristics in chemical production and meet the needs of high-end applications. For example, when synthesizing high-performance plastics, fibers, rubbers and other materials, low-sulfur aromatics can ensure that the products have better stability, strength and durability. Therefore, how to reduce the sulfur content in fuel aromatics has become the focus of researchers.

[0003] Hydrodesulfurization technology (HDS) is a widely used method for removing sulfur compounds in petroleum processing. It can effectively remove sulfur compounds such as mercaptans, sulfides, and disulfides in fuel oil, but the desulfurization effect on thiophene and its derivatives is poor. This is because the CS bond in aromatic sulfides is strong, and catalytic hydrogenation requires more stringent conditions to destroy its structure, often requiring high temperature (>300℃), high pressure (>4MPa), a large amount of catalyst and a large amount of hydrogen, with high energy consumption and operating costs. In addition, during the hydrodesulfurization process, some aromatics will undergo hydrogenation saturation reactions and convert into cycloalkanes or paraffins, resulting in a decrease in the yield of aromatics. Therefore, it is urgent to develop a deep desulfurization technology that can effectively remove thiophene sulfides from aromatics. Adsorption desulfurization technology (ADS) has attracted widespread attention from academia and industry due to its many advantages such as low cost, mild operating conditions, and no reduction in aromatic yield. It is considered to be one of the most promising ultra-deep desulfurization technologies.

[0004] Suitable adsorbent carriers are helpful to improve the performance of adsorbents. Currently, commonly used adsorbent carriers include activated carbon, zeolite molecular sieves, metal oxides, metal organic frameworks (MOFs) and aerogels. Among them, aerogel is a porous material with a three-dimensional network skeleton structure. It has the characteristics of ultra-low density, high porosity, high specific surface area, and adjustable skeleton structure. It is widely used in the field of adsorption and separation. Patent CN112473573B hybridizes dopamine hydrochloride and tetraethyl silicate and dopes Pd 2+ The Pd(II)-DA-SiO2 composite aerogel was prepared by a method. Although the composite aerogel has a high adsorption desulfurization performance, it will also adsorb a part of the aromatic hydrocarbons while adsorbing the sulfide in the simulated aromatic hydrocarbons. Patent CN110354809B hybridizes 3-aminopropyltriethoxysilane and tetraethyl silicate and doped with Ag + SiO2-APTES-Ag composite aerogel was prepared in this way. The composite aerogel also has high adsorption and desulfurization performance. However, due to the fast hydrolysis rate of APTES, SiO2-APTES-Ag needs to be kept below 273K during the sol-gel process, and the preparation steps are relatively cumbersome. The above two types of composite aerogels are both hydrophilic composite aerogels. The presence of polar compounds in aromatic hydrocarbons will reduce the selectivity of this type of composite aerogel for thiophene sulfides. In addition, long-term exposure of hydrophilic aerogel adsorbents to a humid environment will cause their structure to collapse and their adsorption performance to decrease significantly. Summary of the invention

[0005] In view of the above-mentioned defects, the object of the present invention is to provide a preparation method and application of a hydrophobic La / SiO2@DA composite aerogel.

[0006] The specific preparation scheme is as follows:

[0007] A method for preparing a hydrophobic La / SiO2@DA composite aerogel. The hydrophobic La / SiO2@DA composite aerogel is prepared based on a sol-gel method combined with a normal pressure drying technology. The specific preparation steps are as follows:

[0008] 1) preparing a hydrophobic composite alcohol gel: dissolving dopamine hydrochloride in water, adding a hydrophobic silicon source (methyltriethoxysilane) and anhydrous ethanol, stirring and hydrolyzing the mixture under an acidic condition of about pH 2 to obtain a hydrophobic silica sol, adjusting the pH of the silica sol and placing the mixture in a water bath at 40° C. to obtain a hydrophobic composite alcohol gel;

[0009] 2) Aging: adding an aging solution composed of acetone and methyltriethoxysilane to the hydrophobic composite alcohol gel prepared in step 1), and aging in a water bath at 40-50° C. for a period of time to strengthen its skeleton structure;

[0010] 3) Replacement: grind the hydrophobic composite alcohol gel after aging in step 2) and wash with n-hexane;

[0011] 4) Modification: Add n-hexane to the hydrophobic gel obtained in step 3), dissolve lanthanum nitrate hexahydrate in ethanol, and then add the mixture to the gel, stir and let stand;

[0012] 5) Drying: The hydrophobic composite alcohol gel obtained in step 4) is placed at 120° C. and dried under normal pressure to finally obtain a hydrophobic La / SiO2@DA composite aerogel.

[0013] Furthermore, methyltriethoxysilane is used as a silicon source, dopamine hydrochloride is used as an ammonia source, and lanthanum nitrate hexahydrate is used as a lanthanum source, wherein the feed ratio of methyltriethoxysilane to dopamine hydrochloride (the molar ratio of the silicon element added in step 1) to the nitrogen element added in step 1)) is 1:27-432, preferably 1:108, and the feed ratio of methyltriethoxysilane to lanthanum nitrate hexahydrate (the molar ratio of the silicon element added in step 1) to the lanthanum element added in step 4)) is 1:249-996, preferably 1:498.

[0014] An application of a hydrophobic La / SiO2@DA composite aerogel prepared by the above-mentioned preparation method, the operation steps are as follows: quantitatively loading the obtained adsorbent into an adsorption bed device, and introducing simulated aromatic hydrocarbons containing thiophene compounds into the adsorber device at room temperature for adsorption. The simulated aromatic hydrocarbons are divided into two categories, one category of simulated aromatic hydrocarbon products includes aromatic hydrocarbons and thiophene sulfides, and the other category of simulated aromatic hydrocarbon products includes aromatic hydrocarbons, thiophene compounds and polar compounds, the polar compounds are pyridine or water, and the thiophene compounds are thiophene, benzothiophene or dibenzothiophene.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1) The hydrophobic La / SiO2@DA composite aerogel adsorbent of the present invention has La 2+ , -NH2, -CH3, benzene ring, so that the adsorbent can form SM bonds, hydrogen bonds and π-π stacking with thiophene compounds, and can effectively adsorb thiophene compounds;

[0017] 2) Compared with the hydrophilic aerogel, the hydrophobic La / SiO2@DA composite aerogel of the present invention can still have a higher selectivity for thiophene when polar substances such as water or pyridine exist in the simulated aromatic products;

[0018] 3) The dopamine used in the hydrophobic La / SiO2@DA composite aerogel of the present invention is a bio-derived material, which has good biocompatibility, renewability, natural non-toxicity, pollution-free and wide sources. At the same time, the hydrophobic composite aerogel is prepared by a sol-gel method at room temperature combined with normal pressure drying technology. The preparation conditions are mild, the process is simple, the equipment requirements are low, and it is convenient for industrial production. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0020] Examples 1 to 5: Preparation of hydrophobic SiO2@DA composite aerogel adsorption adsorbents with different feed ratios of methyltriethoxysilane and dopamine hydrochloride (silicon / nitrogen molar ratio)

[0021] Example 1: When the feed ratio of methyltriethoxysilane to dopamine hydrochloride (silicon / nitrogen molar ratio) is 54:1, a hydrophobic La / SiO2@DA composite aerogel is prepared, and the preparation method steps are as follows:

[0022] 1) Dissolve 0.08 g dopamine hydrochloride in 6 ml deionized water, then add 10 ml anhydrous ethanol and 4.6 ml methyltriethoxysilane in sequence, adjust the pH of the solution to about 2 with dilute hydrochloric acid solution, and stir at room temperature for 2 h to mix evenly and hydrolyze.

[0023] 2) Add 20% wt ammonia water to the silica sol obtained in step 1), adjust the pH of the solution to about 6.5, and place it in a 40° C. water bath for 3 h to obtain a hydrophobic composite alcohol gel.

[0024] 3) Add 40 ml of a mixed solution of methyltriethoxysilane and acetone in a volume ratio of 15:25 to the hydrophobic composite alcohol gel obtained in step 2), and place in a 50° C. water bath for aging for 18 hours to enhance the skeleton structure of the gel.

[0025] 4) The hydrophobic composite alcohol gel after aging in step 3) was taken, crushed, and washed and replaced with n-hexane. The n-hexane was replaced every 6 hours, and replaced 3 times to remove ethanol, water and other organic molecules in the pores of the gel. Finally, it was dried at 120°C for 12 hours to obtain a hydrophobic SiO2@DA composite aerogel with a silicon / nitrogen molar ratio of 54:1.

[0026] Embodiments 2 to 5

[0027] The hydrophobic SiO2@DA composite aerogels with silicon / nitrogen molar ratios of 72:1, 108:1, 216:1 and 432:1 respectively have the same specific preparation steps as Example 1, except that the added amounts of dopamine hydrochloride in Examples 2 to 5 are 0.06 g, 0.04 g, 0.02 g and 0.01 g respectively.

[0028] Example 6: The hydrophobic SiO2@DA composite aerogel prepared in Examples 1 to 5 was subjected to a penetration adsorption experiment on thiophene sulfides in simulated aromatic hydrocarbons. The specific penetration adsorption experimental steps are as follows:

[0029] In the fixed bed adsorption device, the bottom layer is filled with an appropriate amount of absorbent cotton, and then filled with 1g of the hydrophobic SiO2@DA composite aerogel prepared by Example 1-5, and the top is filled with an appropriate amount of quartz sand. Before the adsorption experiment begins, the filled adsorbent is fully moistened with n-heptane, and then simulated aromatics (MF-1, simulated aromatic components: p-xylene + 0.525wt% thiophene) are introduced. The simulated aromatics after adsorption are collected at the lower end outlet of the fixed bed and chromatographically analyzed. When the sulfur concentration in the effluent is 0.005mgS / g, it is determined as the breakthrough point. The adsorption results are shown in Table 1.

[0030] Table 1 Effect of different silicon / nitrogen molar ratios on the adsorption performance of hydrophobic SiO2@DA composite aerogels for thiophene sulfides in simulated aromatic hydrocarbons

[0031]

[0032] It can be seen from Table 1 that with the increase of the feed ratio of methyltriethoxysilane to dopamine hydrochloride (silicon / nitrogen molar ratio), the penetration adsorption capacity of the hydrophobic SiO2@DA composite aerogel for thiophene first increases and then decreases, and the optimal value is when the silicon / nitrogen molar ratio is 108:1.

[0033] Examples 7-10: Effect of silicon / lanthanum molar ratio on the adsorption performance of hydrophobic La / SiO2@DA composite aerogels for thiophene sulfides in simulated aromatic hydrocarbons.

[0034] Example 7

[0035] The preparation method is the same as that in Example 3 (fixing the silicon / nitrogen molar ratio to 108:1), except that in step 4), after the third n-hexane washing to replace the impurities in the hydrophobic composite alcohol gel, 0.04 g of lanthanum nitrate hexahydrate is dissolved in 5 ml of anhydrous ethanol, and then added dropwise to the hydrophobic alcohol gel solution, stirred at room temperature for 1 h, a lanthanum source is introduced, and finally dried at 120°C for 12 h to obtain a hydrophobic La / SiO2@DA composite aerogel with a silicon / lanthanum molar ratio of 249:1.

[0036] Embodiments 8 to 10

[0037] The hydrophobic La / SiO2@DA composite aerogels with silicon / lanthanum molar ratios of 332:1, 498:1 and 996:1, respectively, have the same specific preparation steps as Example 6, except that the added amounts of lanthanum nitrate hexahydrate in Examples 8 to 10 are 0.03 g, 0.02 g and 0.01 g, respectively.

[0038] The penetration adsorption experiments of Examples 7 to 10 are the same as those of Example 1, and the results are shown in Table 2.

[0039] Table 2 Effect of different silicon / lanthanum molar ratios on the adsorption performance of thiophene sulfides in simulated aromatic hydrocarbons on hydrophobic La / SiO2@DA composite aerogels

[0040]

[0041] It can be seen from Table 2 that with the increase of the feed ratio of methyltriethoxysilane to lanthanum nitrate hexahydrate (silicon / lanthanum molar ratio), the penetration adsorption capacity of the hydrophobic La / SiO2@DA composite aerosol for thiophene first increases and then decreases, among which the optimal value is when the silicon / nitrogen molar ratio is 498:1.

[0042] Examples 11-12

[0043] The effect of the presence of pyridine or water in simulated aromatic hydrocarbons on the adsorption performance of thiophene sulfides in simulated aromatic hydrocarbons on hydrophobic La / SiO2@DA composite aerogel.

[0044] The hydrophobic La / SiO2@DA composite aerogel (silicon / nitrogen molar ratio of 108:1, silicon / lanthanum molar ratio of 498:1) prepared in Example 9 was selected, and the penetration adsorption experiment operation was the same as in Example 6, except that the simulated aromatic hydrocarbons used were MF-2 (p-xylene + 0.525wt% thiophene + 1wt% pyridine) and MF-3 (p-xylene + 0.525wt% thiophene + 1wt% water).

[0045] Comparative Examples 1 to 3

[0046] The effect of the presence of pyridine or water in simulated aromatic hydrocarbons on the adsorption performance of thiophene sulfides in simulated aromatic hydrocarbons on hydrophilic La / SiO2@DA composite aerogel.

[0047] Comparative Example 1

[0048] The preparation method of Comparative Example 1 is the same as that of Example 1, except that the methyltriethoxy in step 1) and step 3) is replaced by tetraethyl orthosilicate, the amount of tetraethyl orthosilicate added in step 1) is 8 ml, the amount of dopamine hydrochloride added is 0.063 g, and when the impurities in the hydrophilic composite alcohol gel are replaced by the third n-hexane washing in step 4), 0.031 g of lanthanum nitrate hexahydrate is dissolved in 5 ml of anhydrous ethanol, and then added dropwise to the alcohol gel solution, stirred at room temperature for 1 h, and a lanthanum source is introduced to prepare a hydrophilic La / SiO2@DA composite aerogel adsorbent having a silicon / nitrogen molar ratio of 108:1 and a silicon / lanthanum molar ratio of 498:1.

[0049] The hydrophilic La / SiO2@DA composite aerogel prepared in Comparative Example 1 was selected, and the penetration adsorption experiment was performed in the same manner as in Example 6, except that the simulated aromatic hydrocarbon used was MF-1

[0050] (p-xylene + 0.525wt% thiophene), MF-2 (p-xylene + 0.525wt% thiophene + 1wt% pyridine), MF-3 (p-xylene + 0.525wt% thiophene + 1wt% water).

[0051] The penetration adsorption results of Examples 11 to 12 and Comparative Examples 1 to 3 are shown in Table 3.

[0052] Table 3 Effect of pyridine in simulated aromatics on the desulfurization adsorption performance of La / SiO2@DA composite aerogel

[0053]

[0054] As can be seen from Table 3, when pyridine is present in the simulated aromatic hydrocarbons, the adsorption capacity of the two composite aerogel adsorbents for thiophene sulfides is reduced, but compared with the hydrophilic La / SiO2@DA composite aerogel, the hydrophobic La / SiO2@DA composite aerogel still shows a higher selectivity for thiophene in the simulated aromatic hydrocarbons. When 1wt% water is present in the simulated fuel, the adsorption selectivity of the hydrophilic La / SiO2@DA composite aerogel for thiophene is significantly reduced by 30%, while the hydrophobic La / SiO2@DA composite aerogel is little affected by water. When water is present in the simulated aromatic hydrocarbons, the adsorption performance of the hydrophobic La / SiO2@DA composite aerogel for thiophene in the simulated aromatic hydrocarbons decreases by only 2%, while the adsorption performance of the hydrophilic La / SiO2@DA composite aerogel for thiophene in the simulated aromatic hydrocarbons decreases by 30%.

[0055] Examples 13-14

[0056] Effect of thiophene sulfide type on the adsorption performance of thiophene sulfides in simulated aromatic hydrocarbons on hydrophobic La / SiO2@DA composite aerogels.

[0057] The hydrophobic La / SiO2@DA composite aerogel prepared in Example 9 was selected, and its penetration adsorption experiment was the same as that in Example 6, except that simulated aromatic hydrocarbons MF-4 (p-xylene + 0.838wt% benzothiophene) and MF-5 (p-xylene + 1.16wt% dibenzothiophene) were used respectively. The penetration adsorption results are shown in Table 4.

[0058] Comparative Examples 4-5

[0059] Effect of thiophene sulfide type on the adsorption performance of thiophene sulfides in simulated aromatic hydrocarbons on hydrophilic La / SiO2@DA composite aerogel.

[0060] The hydrophilic La / SiO2@DA composite aerogel prepared by Comparative Example 1 was selected, and its penetration adsorption experiment operation was the same as that of Example 6, except that simulated aromatic hydrocarbons MF-4 (p-xylene + 0.838wt% benzothiophene) and MF-5 (p-xylene + 1.16wt% dibenzothiophene) were used respectively.

[0061] The penetration adsorption test results of Examples 13-14 and Comparative Examples 4-5 are shown in Table 4.

[0062] Table 4 Adsorption performance of La / SiO2@DA composite aerogels for different thiophene sulfides in simulated aromatic hydrocarbons

[0063]

[0064]

[0065] It can be seen from Table 4 that with the increase of the molecular weight of thiophene sulfides, the penetration adsorption capacity of both hydrophilic and hydrophobic La / SiO2@DA composite aerogels for thiophene sulfides in simulated aromatic hydrocarbons will increase accordingly, but the hydrophobic La / SiO2@DA composite aerogels show a higher adsorption capacity for benzothiophene and dibenzothiophene.

Claims

1. A method for preparing a hydrophobic La / SiO2@DA composite aerogel, wherein the composite aerogel is prepared based on a sol-gel method combined with a normal pressure drying technology, characterized in that: The specific preparation steps are as follows: 1) preparing a hydrophobic composite alcohol gel: dissolving dopamine hydrochloride in water, adding hydrophobic silicon source methyltriethoxysilane and anhydrous ethanol, stirring and hydrolyzing under acidic conditions with a pH value of 2 to obtain a hydrophobic silica sol, adjusting the pH of the silica sol and placing it in a 40° C. water bath to obtain a hydrophobic composite alcohol gel; 2) Aging: adding an aging solution composed of acetone and methyltriethoxysilane to the hydrophobic composite alcohol gel prepared in step 1), and aging in a water bath at 40-50° C. to enhance its skeleton structure; 3) Replacement: grind the hydrophobic composite alcohol gel after aging in step 2) and wash with n-hexane; 4) Modification: Add n-hexane to the hydrophobic gel obtained in step 3), dissolve lanthanum nitrate hexahydrate in ethanol, and then add the mixture to the gel, stir and let stand; 5) Drying: The hydrophobic composite alcohol gel obtained in step 4) is placed at 120° C. and dried under normal pressure to finally obtain a hydrophobic La / SiO2@DA composite aerogel.

2. The method for preparing a hydrophobic La / SiO2@DA composite aerogel according to claim 1, characterized in that: The molar ratio of the silicon element added in step 1) to the nitrogen element added in step 1) is 1:27-432, preferably 1:

108.

3. The method for preparing a hydrophobic La / SiO2@DA composite aerogel according to claim 1, characterized in that: The molar ratio of the silicon element added in step 1) to the lanthanum element added in step 4) is 249-996:1, preferably 498:

1.

4. An application of a hydrophobic La / SiO2@DA composite aerogel prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The application is to adsorb and remove thiophene sulfides in simulated aromatic hydrocarbons. The thiophene compounds are thiophene, benzothiophene or dibenzothiophene. The simulated aromatic hydrocarbons are divided into two categories. One category of simulated aromatic hydrocarbon products includes aromatic hydrocarbons and thiophene sulfides; the other category of simulated aromatic hydrocarbon products includes aromatic hydrocarbons, thiophene compounds and polar compounds. The polar compounds are pyridine or water.

Citation Information

Patent Citations

  • Preparation method and application of dopamine / silicon dioxide composite aerogel

    CN112452262A

  • Preparation method and application of SiO2-APTES-La composite aerogel

    CN112473574A

  • Preparation method of hydrophobic rare earth-based silicon dioxide aerogel

    CN116692881A

  • Preparation method and application of hydrophobic Pd (II) / SiO2 (at) APTES composite aerogel

    CN117619354A

Cited By

  • Method for preparing hydrophobic La-Al / SiO2 composite aerogel desulfurization adsorbent by micro-droplet template method and application of hydrophobic La-Al / SiO2 composite aerogel desulfurization adsorbent

    CN122164361A